Scientific and Educational Activities of the Institute “Microbe” during the Great Patriotic War - S. V. Generalov (Проблемы особо опасных инфекций, 2025)
The paper discusses the organization of research and educational activities of the Institute “Microbe” during the Great Patriotic War. The main scientific achievements and contribution of the institute’s employees to ensuring the epidemiological well-being of the country are outlined. The methodological basis for the study was the documents from the funds of the “Microbe” Institute and the State Archives of the Saratov Region (SASR). The presented photographic material is published for the first time.